Estética e dessubjetivação em Deleuze - Leandro Lelis Matos (2021)
The aim of this thesis is to investigate the problem of aesthetics in Deleuze from the concept of desubjectivation. The starting point of the work is the hypothesis that the question of aesthetics may be one of the main ways to guide a reading of Deleuzian thought, above all, with regard to a new way of thinking independently of subjective rationality. The verification of this hypothesis will go through four necessary and decisive moments: 1) the approach of the concept of difference in itself that will provide us with the indispensable basis to think the question of aesthetics in the key of sensation. 2) The appropriation of the concept of repetition in dialogue with pre-subjective syntheses in time and in the unconscious. Along with the difference, this powerful and important Deleuzian concept of repetition aims to release the thought of its traditional bond or obstacle, a kind of impediment that runs through perhaps the entire history of Western philosophy from modernity to today, which is the representation. 3) The analysis of the notion of transcendental empiricism, whose bases are no longer subordinated to the subject and object coordinates, as a legitimate and unprecedented proposal by Deleuze for a sensitive thought. 4) Finally, the path through the relationship between body and language in order to investigate to what extent the problem of aesthetics in Deleuze is produced more as a “practice”, which is freed from the (theological) system of judgment, is capable of giving rise to new modes of existence.